Comparison Analysis of Conventional Method Floor Slabs With Half Slab Method Against Cost and Time of XYZ Project - Novika Candra Fertilia; Muhammad Fadhiil Dwi Sukmana (NAROTAMA UNIVERSITY, Indonesia, 2021)
Development in the infrastructure and construction sector in Indonesia has been growing from year to year both in terms of design and the system used. Some of these systems include conventional and precast (Half Slab) systems. Implementation of the conventional system is casting on site or it can be called Cast in situ, while the precast for the implementation of the production process is carried out in a special place, then taken to the project site (transportation) to be compiled into one intact structure. In the implementation of the conventional system there are several shortcomings, namely it takes a long time, is of poor quality and requires a lot of formwork and workers, resulting in a long implementation time. But behind these many shortcomings, of course, there are advantages, namely low implementation costs. In this research, the writer will compare the conventional floor slab system with the half slab floor plate on the bridge project as the object of this final project to compare the effect between the conventional system and the half slab on the project implementation cost requirements and the implementation period and the implementation method. The comparative analysis of the conventional method floor slab and the half slab method floor plate has obtained results. For the conventional method floor plate costs Rp. 2,353,749,140 with an implementation time of 67 days. While the half slab floor plate costs Rp. 2,598,711,750 with an implementation time of 49 days. So conventional floor plate work is cheaper by Rp. 244,962.